The importance of dysregulated miRNAs on ovarian cysts and epithelial ovarian cancer - Gumusoglu, Ece; Gunel, Tuba; Hosseini, Mohammad Kazem; Seymen, Nogayhan; Senol, Taylan; Sezerman, Ugur; Topuz, Samet; Aydinli, Kilic (IMR PRESS, 2021)
Objective: Benign ovarian cysts (BOC) are the most common tumors in women of reproductive age. Usually, these cysts are harmless, but, a small number of them occasionally progress to malignancy. Among ovarian malignancies, epithelial ovarian cancer (EOC) comprises 90\% and is the most important cause of gynecologic cancerrelated deaths. We aimed to identify dysregulated miRNAs in patients with benign ovarian cysts (n = 11) compared to EOC (n = 10) and to healthy individuals (HI) (n = 15). Methods: The serum samples from EOC and BOC patients were collected before operation. We studied three different sample groups (serum of EOC (n = 8), HI (n = 8), and BOC (n = 8) patients) that contained the highest-quality of RNA. Microarray data were analyzed according to expression of miRNAs and target genes by bioinformatics tools. Results: When compared to EOC samples, 75 miRNAs were dysregulated in BOC samples. Sixty-six miRNAs from BOC were dysregulated when compared to HI samples. Bioinformatics analysis of BOC vs. EOC and BOC vs. HI showed that 46 miRNAs were congruent and their expression alterations were similar (up- or down-regulated). Further analysis showed that these 46 miRNAs are associated to one of three pathways involved in cancer pathogenesis. Conclusion: Several miRNAs might playa role in BOC formation and/or malignant transformation. These dysregulated miRNAs could potentially be a biomarker to distinguish between a completely BOC and one that is malignant or has potential for malignant transformation.
Keywords: Ovarian neoplasms; Ovarian cysts; MicroRNAs; Neoplastic transformation; Epithelial ovarian cancer